Design and Characterization of an AOTF Hyper-Spectral Polarization Imaging System. Issue 1 (2nd January 2017) - Wang, Qichao; Shi, Jiaming; Wang, Jiachun; Zhao, Dapeng; Liu, Yang
Abstract: The present paper describes a hyper-spectral polarization imaging system based on a non-collinear, acousto-optic tunable filter (AOTF) and a linear polarizer. The paper begins with an analysis of the equivalent relationship of the AOTF to describe the principle of polarization detection of this system. Appropriate parameters of hardware components are assigned later. This system, being electronically controllable and tunable, can not only ensure the precision of imaging but also obtain hyper-spectral polarization signatures. The prototype has two optional working modes, namely, hyper-spectral polarization imaging and hyper-spectral intensity imaging. Moreover, parameters of this system – such as diffraction efficiency, spectral resolution and modulation precision – are tested using a halogen tungsten lamp and an optical fibre spectrometer. The results indicate that this instrument is compact, vibration-insensitive, robust and precisely controllable. The system designed in this paper has further application in polarization detection techniques in military.